PELATIHAN CABANG OLAHRAGA BELADIRI PENCAK SILAT TENTANG TEKNIK DASAR TENDANGAN T PRAYA TENGAH - Herlina, Herlina; Nulhadi, Agus; Burhan, Zakir; Ashari, Lalu Hasan (Insanta : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service highlights the importance of self-defense for children, because crime is currently rampant in schools and Islamic boarding schools, and incidents of bullying often occur and even result in death. Therefore, you need to learn self-defense techniques to anticipate this, namely self-defense. There are various kinds of pencak silat branches around us, both domestically and internationally. One of them is Pencak Silat. Pencak Silat is a martial arts science originating from Indonesia. Pencak Silat aims not only to learn martial arts and self-defense, but also to instill a moral attitude and increase devotion to Allah SWT.